Sociomuseology and post-procedural Archeology: connections in the contemporary Brazilian context. (Cadernos de Sociomuseologia, 2016)
In this article I summarize fundamental aspects of the musealization processes of archaeological heritage. I shall start this text with a short description of the field of archeology in Brazil; presenting then, the design of some assumptions which have guided the construction of this research, emphasizing the necessary interface between Archeology and Museology. I will also introduce the interweaving between Sociomuseology and the strands of post-procedural archeology as a way of overcoming the obstacles evidenced in the contemporary context. In conclusion, I shall synthesize the thesis’ case study, where I have applied the prospects of Sociomuseology in designing a program of socialization of the archeological resources rescued under the Transnordestina Railroad. The outline of the program was understood while synthesis of the complex, however necessary, web of relations between Museology and Archeology in a contemporary Brazilian scenario was made. Keywords: Archaeological heritage; Archeology and museology; post-procedural archeology.